Peningkatan Pengetahuan Kelompok Tani Aren melalui Pelatihan Usaha Gula Aren di Kabupaten Maros, Sulawesi Selatan - makkarennu makkarennu; Supratman Supratman; Diyah Yumeina (Institut Pertanian Bogor, 2022)
Palm sugar as one of the non-timber forest products commonly used by communities around the forest area to be processed into palm sugar that can be sold to make ends meet. Community service activities is carried out in one of the villages adjacent to the Hasanuddin University Educational Forest Village Rompegading Cenrana Maros District of South Sulawesi province. The purpose of the implementation of this activity is to increase the quality of palm sugar processers who are part of the Palm Sugar Farmer Group through training and mentoring. This is based on the problems faced by the group, namely the low knowledge of the community in the processing of palm sugar, production process, product diversification, packaging and marketing. The number of trainees as many as 20 people who are the target partners of the group Tani Moncong Jai. The implementation of the activity is carried out through several stages, namely the preparation stage, introduction of activities, implementation of training and evaluation stage. The external target that has been achieved is the improvement of participants' knowledge of the materials submitted. The results of the pre-test and post-test showed that there was a 30% increase in the knowledge of farm group members related to the handling of raw materials, 53% product diversification, and 34% marketing. In addition, there is a design of printed palm sugar that can be used to market their products.